Geographical Distribution of Fungal Plant Pathogens in Dust Across the United States - Dietzel, Kristin; Valle, Denis; Fierer, Noah; U'Ren, Jana M.; Barberán, Albert (Frontiers in Ecology and Evolution, 2019)
As the world's population grows, global food production will need to increase. While food production efficiency has increased in recent decades through pathogen control, climate change poses new challenges in crop protection against pathogens. Understanding the natural geographical distribution and dispersal likelihood of fungal plant pathogens is essential for forecasting disease plant spread. Here we used cultivation-independent techniques to identify fungal plant pathogens in 1,289 near-surface dust samples collected across the United States. We found that overall fungal pathogen community composition is more related to environmental conditions (in particular soil pH, precipitation and frost) than to agricultural hosts and practices. We also delimited five susceptibility geographical areas in the United States where different sets of pathogens tend to occur.